Electromechanical Reshaping of Porcine Eustachian Tube Cartilage Ex Vivo - Yoon, Byungwoo; Koo, Soo-Kweon; Baek, Moo-Jin; Lee, Il-Woo; Oh, Se-Joon; Kong, Soo-Keun (Journal of audiology & otology, 2025)
Background and Objectives: The Eustachian tube cartilage (ETC) is the cartilaginous frame of the Eustachian tube (ET), which plays a pivotal role in its function. Existing treatments for ET dysfunction (ETD) are primarily based on mechanical deformation. Electromechanical reshaping (EMR) is a novel method used to reshape the cartilage into the desired form by applying an electric current using strategically placed needles for mechanical deformation. In this study, EMR was evaluated for its ability to reshape the ETC.Materials and Methods: A total of 84 ETCs were harvested from 42 post-mortem porcine crania and randomly divided into control and experimental (EMR) groups. To reshape the ETC, the control ETCs were subjected to a mechanical force, whereas the experimental group was subjected to the same force and current of 3, 4, or 5 V for 2 or 3 min. Changes in shape were assessed by measuring the contour angles using digital photographs.Results: In the analysis of the contour angle, ETC post-EMR for 2 min at ≥4 V demonstrated significant reshaping relative to the control group (p<0.05).Conclusions: EMR can be used to reshape the ETCs ex vivo. Future experiments with well-designed ex vivo and in vivo conditions are required to develop novel therapeutic options for ETD.